A Semantic Study of Swearing Used by Mountainous People in Regional West Yemen - Al-Hamzi, Ali Mohammed Saleh; Prastyo, Hari; Annuzaili, Abdulwadood Ahmed (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2024)
Meaning is the core unit of language. It may convey positive and negative implications. Swearing is an intriguing language-related topic. Hence, this work is carried out to discover and describe the form, reference, meaning, and purpose of swearing in Yemeni Arabic as practiced by the people in mountainous regions of western Yemen. People express their feelings through the use of utterances that are referred to as swearing. These utterances typically have a negative connotation. This qualitative research presents the spoken language utilized by the respondents residing within the sub-districts of the Mahweet and Hajjah provinces in western Yemen. The data processing consisted of three stages: choosing, transcribing, and evaluating relevant data. The form, reference, and function of swearing were all interpreted to conduct the analysis. There were many other ways to swear, including monomorpheme, polymorpheme, phrase, clause, and sentence forms. Those swearing forms are referred to animals, religious terms, supernatural creatures, members of the family, portions of the body, human activities, professions, oaths, illnesses, and exclamations. Connotatively and denotatively, the swearing allowed for rage, displeasure, surprise, insult, and even humor. The study's implications were also studied. As a result, researchers may undertake more thorough investigations to better understand urban or coastal Yemeni swearing. The sociolinguistic, discursive, and pragmatic aspects of swearing should be researched more in the future.